Réponses

  • Utilisateur Brainly
2014-05-24T14:03:41+02:00
Bonjour, 

a) 3(2 -3y) = -(y -2)
6 - 9y = - y + 2
6 - 2 = - y + 9y
4  = 8y
4/8 = y
1/2 = y

S= {1/2}

b) -2(a -1) = 4 (2a +1)
- 2a + 2 = 8a + 4
- 2a - 8a = 4 - 2
- 10a = 2
- a = 2/10
a = - 2/10
a = - 1/5

S= {-1/5}
2014-05-24T14:18:09+02:00
a) 
3(2 -3y) = -(y -2)
3*2+3*(-3y)=-y+2
6-9y=-y+2
6-9y-6+y=-y+2-6+y
-8y=-4
y=-4/-8
y=1/2


b) 
-2(a -1) = 4 (2a +1)
-2*a-2*(-1)=4*2a+4*1
-2a+2=8a+4
-2a+2-2-8a=8a+4-8a-2
-10a=2
a=2/-10
a=1/-5

voilà :)